Evaluating the effects of guide plans on the mental health of villagers (Case study: Central district of Darab County) - Hamid Heidary mokarrar; Hamid reza Nasimi; Zohreh Ramezanpour (تحقیقات کاربردی علوم جغرافیایی)
Various developmental proceedings of conducting guide plans have been considered as one of the main prerequisites for social welfare by providing a basis for comprehensive development and improvement of living conditions in the rural areas and promoting the mental health of villagers. Accordingly, the present research seeks to evaluate the effects of guide plans on the mental health status of villagers in the central part of Darab County. This research is a descriptive-analytic study in which the documentary method used to examine the records and explain the problem, a survey method was used to collect data using observation, interview, and completion of questionnaire among the villagers. Descriptive, inferential and spatial analysis was performed using Excel, SPSS and ArcGIS software to analyze the data. The findings of the study confirm that the executive measures of the conducting guide plans in the studied villages are in a proper level. Accordingly, the quality of implementation of these plans, at a confidence level of 0.99, is correlated with the mental health of the villagers. Also, the results of regression test showed that about 20% of the changes in mental health status of the people living in the studied villages were predicted by the implementation of guide plans. Other results of the research confirm that there is a significant difference between mental health status in all three age groups of men But among women, there is a significant difference between the two age groups of the elderly with young people and middle aged people.